The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12873-020-00330-1
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive skills of emergency medical services crew members: a literature review

Abstract: Background: Situation awareness and decision making, listed in non-technical skills taxonomies, are critical for effective and safe performance in high-risk professions. These cognitive skills and their behavioral markers have been studied less in emergency medical services (EMS) crew members. This paper aims to review the existing literature and identify important aspects and behavioral markers of situation awareness and decision making in EMS crew membersthose who work in the role of prehospital emergency ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Clinical reasoning has attracted significant research interest, especially in hospital contexts. While these studies often focus on physicians and patient safety, some recent work has taken a broader view (Andersson et al, 2019; Perona et al, 2019; Sedlár, 2020), with increased attention to CR in EMS contexts. Much of the extensive research on CR relates to diagnosis, including the accuracy of EMS field diagnoses as compared to hospital discharge diagnoses (Magnusson et al, 2020; Wilson et al, 2018) and difficulties in assessing or managing conditions like sepsis (Sjösten et al, 2019), stroke (Andersson et al, 2018) or cases involving resuscitation (Andersson et al, 2021; Brandling et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical reasoning has attracted significant research interest, especially in hospital contexts. While these studies often focus on physicians and patient safety, some recent work has taken a broader view (Andersson et al, 2019; Perona et al, 2019; Sedlár, 2020), with increased attention to CR in EMS contexts. Much of the extensive research on CR relates to diagnosis, including the accuracy of EMS field diagnoses as compared to hospital discharge diagnoses (Magnusson et al, 2020; Wilson et al, 2018) and difficulties in assessing or managing conditions like sepsis (Sjösten et al, 2019), stroke (Andersson et al, 2018) or cases involving resuscitation (Andersson et al, 2021; Brandling et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This thesis has, in line with previous research, indicated situational awareness 23 as a foundational aspect in medical assessments, clinical reasoning, clinical decision-making, and patient safety [173][174][175][176][177][178][179][180]. The preceptors used talking aloud during caregiving and created mental schemata for recurring sources of information to support the students to collect the correct cues and avoid cognitive biases in clinical decision-making.…”
Section: Situational Awareness As a Basis For Decision Makingsupporting
confidence: 61%
“…However, the methodological foundations and body of knowledge about coping with stress and communication with patients in paramedic profession are thinner compared to the study of cognitive skills such as decision-making and situation awareness (see Sedlár, 2020) as well as communication skills in team performance (see Manser, 2009). This is due to greater difficulty of assessment of these skills from observable behavior, especially in the case of stress management (Shields & Flin, 2012).…”
Section: Introductionmentioning
confidence: 99%